Peranan Kepala Sekolah Sebagai Supervisor Dalam Meningkatkan Kinerja Guru Pendidikan Agama Islam - Asep Bambang Susanto; Mahardini, Angger Putri; Nazarudin (Institut Agama Islam Darul Fattah Lampung, 2025)
This study aims to describe the role of the principal as a supervisor in improving the performance of Islamic Religious Education (PAI) teachers at SMA Qur'an Darul Fattah. The focus of the study is directed at how the principal designs, implements, and follows up on academic supervision activities to support teacher professionalism. The approach used is descriptive qualitative, with data collection techniques through interviews, observations, and documentation. The study results indicate that the principal carries out his supervisory role systematically, participatively, and humanistically. In the planning stage, the principal involves teachers in preparing a supervision program based on the school's needs and Qur'anic vision. The implementation of supervision is carried out dialogically with a clinical approach, so that teachers feel appreciated and encouraged to develop. Follow-up supervision in the form of internal training, individual mentoring, and ongoing coaching has been proven to improve the competence and motivation of PAI teachers. This study confirms that supervision that is carried out continuously and oriented towards professional coaching can make a real contribution to improving the quality of PAI learning. These findings indicate that the role of the principal is very crucial in creating a work culture that supports improving teacher performance as a whole. In addition, this study recommends the importance of strengthening the capacity of school principals in carrying out effective academic supervision and the need for systemic support from all education stakeholders.